Significance of Low Muscle Mass on Arterial Stiffness as Measured by Cardio-Ankle Vascular Index - Park, Hyo Eun; Chung, Goh Eun; Lee, Heesun; Kim, Min Joo; Choi, Su-Yeon; Lee, Wonjae; Yoon, Ji Won (Frontiers in Cardiovascular Medicine, 2022)
Aim A link between low muscle mass and arterial stiffness is not always consistent. In this study, we aimed to evaluate the clinical significance of low skeletal muscle mass in relation to arterial stiffness measured by the cardio-ankle vascular index (CAVI). Methods A total of 2,561 asymptomatic Korean subjects who underwent bioelectrical impedance analysis (BIA) and CAVI were included for analysis. Using appendicular skeletal muscle mass (ASM), classes I and II sarcopenia were defined as ASM% greater than 1 standard deviation (SD) and 2 SDs below the gender-specific mean of healthy young Korean adults. Results Compared to normal, CAVI was significantly higher, but the number of patients with a low ankle-brachial index (ABI) was not significantly different (p < 0.001 for CAVI, p = 0.078 for ABI). Classes I and II sarcopenia showed an independent and significant association with CAVI (estimate 0.148, standard error (SE) 0.043, p < 0.001 and estimate 0.304, SE 0.073, p < 0.001 for classes I and II sarcopenia, respectively, adjusted for age groups, gender, body mass index (BMI) ≥25, hypertension, diabetes, hypercholesterolemia, and smoking). Conclusion Low muscle mass is independently and significantly associated with increased CAVI, and should be considered when managing asymptomatic subjects to assess the risk of atherosclerosis.